Renegotiating Israeli Identities, Collective Victimhood and Social Exclusion of Arab Israelis in a Changing Social Reality. (March 2019) - Hadar, Maya
This article discusses the changing nature of the Israeli identity and core values against the backdrop of political and social processes that took place in Israel in recent decades. Special attention was given to manifestations of collective victimhood within the framework of the Israeli society and politics and the way the latter obstructed social inclusion of Arab Israelis and of acknowledging commonalities between Jewish and non-Jewish Israelis.